Assessment of Tailoring Training Facilities in Implementation of School-On-Wheel Scheme of National Directorate of Employment in Anambra State of Nigeria - C.C., Anowai; E.U., Anyakoha (Journal of Home Economics Research, 2024)
The study assessed tailoring facilities used in training beneficiaries of School-on-Wheel Scheme of National Directorate of Employment on tailoring occupation in Anambra State. Descriptive survey design was used. The study population was 328. A sample of 103 was drawn using snowball technique plus all the scheme’s 15-tailor-instructors, making the total sample 118. Data were collected using a questionnaire; focus group discussions provided in-depth information. Frequency, mean, standard deviation and t- test were used in data analysis. Nine training facilities were found to be functionally available with six in right quantities. Epileptic power supply rendered few available electrical facilities non-functional. Staff enumeration was adequate, nevertheless, office accommodation, training consumables, take-off grants for beneficiaries were grossly inadequate. Clearer policy framework, adequate funding and further research were recommended by the study.